THE EFFECT OF FINANCIAL RATIO IN THE ALTMAN Z-SCORE ON FINANCIAL DISTRESS - Ayu Suci Pratiwi; Shinta Heru Satoto; Sri Budiwati Wahyu; Suprapti Suprapti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this study is to determine the effect of financial ratio in Altman Z-Score Model, that is Net Working Capital to Total Assets, Retained Earnings to Total Assets, Earnings Before Interest Tax to Total Assets, and Book Value of Equity to Total Liability on the probability of financial distress in manufacturing companies. This research uses purposive sampling method where 39 samples companies are obtained. The criteria for financial distress in this study were measured using the Altman Z-Score. The result show that Net Working Capital to Total Assets and Book Value of Equity to Total Liability has an effect on the probability of financial distress, but Retained Earnings Total Asset and Earnings Before Interest Tax to Total Assets has no effect on the probability of financial distress